Autonomous schools, achievement, and segregation - Irmert, Natalie,Bietenbeck, Jan,Mattisson, Linn,Weinhardt, Felix (CESifo, 2023)
We study whether autonomous schools, which are publicly funded but can operate more independently than government-run schools, affect student achievement and school segregation across 15 countries over 16 years. Our triple-differences regressions exploit between-grade variation in the share of students attending autonomous schools within a given country and year. While autonomous schools do not affect overall achievement, effects are positive for high-socioeconomic status students and negative for immigrants. Impacts on segregation mirror these findings, with evidence of increased segregation by socioeconomic and immigrant status. Rather than creating
10419/282519
Keywords: Graue Literatur; autonomous schools; student achievement; school segregation